Investment Analysis of Ferrari S.p.A - Zhou, Shihao (Transactions on Economics, Business and Management Research, 2024)
This research paper provides a comprehensive investment analysis of Ferrari S.p.A., a renowned Italian luxury sports car manufacturer. The study employs a detailed SWOT analysis to evaluate Ferrari’s strengths, weaknesses, opportunities, and threats, alongside a Porter’s Five Forces analysis to assess the competitive forces within the automotive industry. Additionally, the paper examines Ferrari’s financial health by analyzing historical data, financial statements, and key financial ratios. The findings underscore Ferrari’s brand equity, cutting-edge technological innovations, and efficient cost management practices, collectively enhancing its market competitiveness and financial stability. Furthermore, the paper discusses the strategic initiatives undertaken by Ferrari to maintain its leadership position in the luxury sports car market. This study aims to provide valuable insights for investors considering Ferrari as a potential investment, highlighting its strengths, opportunities, and the challenges it faces in the dynamic global market. By understanding these factors, investors can make informed decisions about the viability of investing in Ferrari.